Reducing Barriers to Breast Imaging in Patients with Mobility Limitations. Issue 1 (2nd January 2020) - Bouhmam, Houda; Romanoski, Natasha L; Chetlen, Alison L
Abstract: Over 1 billion people worldwide live with a disability. Patients living with disability are often challenged by many barriers to healthcare access, especially preventive and screening services. The Americans with Disabilities Act of 1990 mandated that access to public accommodations related to medical care in the United States be available to all; however, many healthcare facilities fall short of meeting this requirement. Research studies suggest that women with chronic disabilities are less likely to undergo breast cancer screening due to financial, environmental, and physical limitations, as well as psychological barriers. There is scarcity of research on the needs of individuals with mobility impairments and the features of the barriers they face when accessing healthcare services, especially breast imaging services. The objective of this article is to illustrate the existing barriers to breast imaging services that individuals with mobility impairments face and to provide a list of guidelines to be used in clinical practice for breast care practices and medical staff working with patients who have mobility impairments.